A Predominant Clonal Thromboembolic Meningoencephalitis Group of Histophilus somni Assigned by Major Outer Membrane Protein Gene Sequencing and Pulsed-Field Gel Electrophoresis - Ueno, Yuichi; Teratani, Chie; Misumi, Wakako; Hoshinoo, Kaori; Takamatsu, Daisuke; Tagawa, Yuichi; Katsuda, Ken (Frontiers in Veterinary Science, 2018)
Histophilus somni, a member of the family Pasteurellaceae, causes a variety of diseases, including thromboembolic meningoencephalitis (TEME) and respiratory diseases, which result in considerable economic losses to the cattle and sheep industries. In this study, 132 chronologically diverse isolates from cattle in Japan and 68 isolates from other countries comprising 49 from cattle and 19 from sheep were characterized using major outer membrane protein (MOMP) gene sequence and pulsed-field gel electrophoresis (PFGE) analyses. The H. somni isolates formed nine MOMP genetic clades (clade Ia, Ib, and II–VIII) and 10 PFGE clusters (HS1–HS10). Except for two (1.0%), all isolates fell into one of the nine MOMP genetic clades, while 62 (31.0%) isolates belonged to no PFGE cluster. MOMP genetic clade Ia and PFGE cluster HS1 were the major groups, and all HS1 isolates possessed the clade Ia MOMP gene. Isolates from TEME cases were significantly associated with these major groups (chi-square test, p < 0.0001), as 88.2% of the TEME isolates belonged to MOMP genetic clade Ia and PFGE cluster HS1, which formed the most predominant clonal group. After an inactivated vaccine using an HS1 strain with the clade Ia MOMP gene was introduced in Japan in late 1989, the number of TEME cases and isolates assigned into the clonal group decreased simultaneously. However, the proportions of clade Ia and cluster HS1 isolates from TEME cases remained high after 1990. These results suggest a close association of TEME with PFGE cluster HS1 and MOMP genetic clade Ia, and imply the presence of factors or characteristics commonly possessed by those strains that contribute to the development of TEME.